Cohomology with bounds and Carleman estimates for the ∂¯-operator on Stein manifolds - Patrick W. Darko (International Journal of Mathematics and Mathematical Sciences)
Cohomology with bounds are used to globalize a result of Hörmander obtaining Carleman estimates for the Cauchy-Riemann operator on Stein manifolds.